Comparison of Rigid and Flexible Medial Arch Supports on Walking Speed in Flat-Footed Patients - Setyawan, Dwi; Septiani, Annisa Eka; Sari, Ketut Intan Yunika (Poltekkes Kemenkes Jakarta I, 2023)
Background: Flat foot patients requires more muscle activity when walking due to lack of medial longitudinal arch arches and results in increased pressure on the second area of metatarsal during the stance phase, causing the gait cycle in flat foot patients to be longer than for children who have normal foot. The speed of walking of flat foot patients can be faster using flexible medial arch support compared to when using rigid medial arch support. Purpose: to determine difference in walking speed using rigid medial arch support and flexible medial arch support in patients with flat foot. Methods: 30 subjects according to inclusion and exclusion criteria. Subject divided into two groups and given treatment using rigid medial arch support and flexible medial arch support the calculating walking speed using 10 Meter Walk Test. Quasi Experiment with Post Test Only Design. Material used (1) rigid medial arch support, (2) flexible medial arch support, (3) midline, (4) stopwatch, (5) HVS paper, (6) liquid color, (7) cone, (8) stationary, (9) measuring form. Results: The average walking speed using rigid medial arch support at the fast walking speed is 1.6800 m/s and the comfortable walking speed is 1.2627 m/s. The average walking speed using flexible medial arch support at the fast walking speed is 1.8140 m/s and the comfortable walking speed is 1.6467 m/s. The results of Shapiro Wilk data (N=15: 15) showed normally distributed data. Therefore, using the parametric test (Independent Sample T-test) obtained p < 0.05. Conclusion: Based on statistical tests, it was found that there was a significant difference in walking speed using rigid medial arch support and flexible medial arch support in patients with flat foot. Based on field data, it was found that comfortable walking speed of rigid medial arch support was faster than the flexible medial arch support by 30.4%.